Discursive narratives of comprehensive education politics in Finland. (September 2018) - Kosunen, Sonja; Hansen, Petteri
In recent years Finnish comprehensive education has often been discussed in both, academic and public forums, in terms of its relatively high learning outcomes and perceived efficiency. Yet what has often been lacking in cross-country comparisons is a critical socio-historical analysis of contingent nation-specific events and features as well as an in-depth analysis of Finnish education politics as constantly changing dynamic system. We analyze and reconstruct the discursive narrative of Finnish comprehensive education within a socio-historical framework. The material consists of interviews with the establishment of Finnish education: politicians, leading policy-makers and stakeholders, and established scholars (n=9). Three periods were recognized and reconstructed in the analysis: 1) The pre-comprehensive school period, 2) a steady development culminating in the crisis of the 1990s, and 3) the PISA results, which in the narrative led to international success and national gridlock. The crucial changes relate to changes in audiences (performing game). Two key findings emerge from this discursive narrative analyses: the role of the PISA reports as a turning point for the basic education politics in Finland and how this turn led to a discussion of comprehensive school as a kind of success story.